Total quality management the first steps - Drozda, Tom; Eade, Robert; Bollinger, Steven R. (Manufacturing insights, 1992)
Explores the corporate changes necessary to implement Total Quality Management (TQM), discusses corporate entities that have made the necessary cultural changes and that have been successful in implementing TQM.